Rapid improvement of respiratory quality in asthmatic children after "assisted drainage" therapy - Haryono Utomo; Ariyanto Harsono (Paediatrica Indonesiana, 2010)
Background Â Whilst current asthma management is well-developed, there are still 5-10% uncontrolled asthma patients with unknown etiologies. However, its connection with oral focal infection is still uncertain. Therefore, a collaborated research for asthma management was conducted by pediatricians and dental practitioners. Within minutes after the "assisted drainage" therapy, a modification of healing root planning procedure, there is rapid improvement of respiratory function, ie., forced expiratory-volume one second (FEV1) in asthmatic children. This quick response usually achieved by oral inhalation.Objective To investigate the effectiveness of the assisted drainage therapy in the improvement of respiratory quality.Methods Fifteen asthmatic children were subjected to a longitudinal study for two weeks. In tbe first week they were instructed for al lergen avoidance only and the fOllowing one week was combined with tbe assisted drainage therapy, followed by Â mental health education and dental plaque control therapy. Each s'ubject was af'sef'sed for respiratory quality with a computerized spirometer and blood sampling test. Paired t-test analysis was used for statistical analysis.Results Assisted drainage therapy was performed, within minutes FEV1 increased significantly (P= 0.001). Additionally, there were significant differences serum histamine (P= 0,001) pre and post treatment.Conclusions The assisted drainage therapy is effective as an adjuvant therapy for mild persistent asthma in children.